Fighting MDR-Klebsiella pneumoniae Infections by a Combined Host- and Pathogen-Directed Therapeutic Approach - Poerio, Noemi; Olimpieri, Tommaso; Henrici De Angelis, Lucia; De Santis, Federica; Thaller, Maria Cristina; D’Andrea, Marco Maria; Fraziano, Maurizio (Frontiers in Immunology, 2022)
Klebsiella pneumoniae (KP) is an opportunistic pathogen very difficult to treat mainly due to its high propensity to acquire complex resistance traits. Notably, multidrug resistance (MDR)–KP infections are responsible for 22-72% of mortality among hospitalized and immunocompromised patients. Although treatments with new drugs or with combined antibiotic therapies have some degree of success, there is still the urgency to investigate and develop an efficient approach against MDR-KP infections. In this study we have evaluated, in an in vitro model of human macrophages, the efficacy of a combined treatment consisting of apoptotic body like liposomes loaded with phosphatidylinositol 5-phosphate (ABL/PI5P), and ϕBO1E, a lytic phage specific for the major high-risk clone of KPC positive MDR-KP. Results show that ABL/PI5P did not affect in a direct manner KKBO-1 viability, being able to reduce only the intracellular KKBO-1 bacterial load. As expected, φBO1E was effective mainly on reducing extracellular bacilli. Importantly, the combination of both treatments resulted in a simultaneous reduction of both intracellular and extracellular bacilli. Moreover, the combined treatment of KKBO-1 infected cells reduced pro-inflammatory TNF-α and IL-1β cytokines and increase anti-inflammatory TGF-β cytokine production. Altogether, our data support the therapeutic value of a combined host- and pathogen-directed therapy as a promising approach, alternative to single treatments, to simultaneously target intracellular and extracellular pathogens and improve the clinical management of patients infected with MDR pathogens, such as MDR-KP.